SEMANTIC FOUNDATIONS OF PUNCTUATION IN ENGLISH: BASED ON THE MATERIALS OF DRAMATIC WORKS - Mansurova Zarifa Olimjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the semantic role of punctuation in English, focusing on how punctuation marks contribute to meaning and interpretation within dramatic works. By analyzing the use of punctuation in dialogue and stage directions, the study investigates how these seemingly small marks influence pace, tone, characterization, and the overall understanding of dramatic texts. The research argues that punctuation is not merely a grammatical convention, but a crucial tool for playwrights to convey nuances of meaning and create specific effects for the audience. The analysis will consider the use of commas, semicolons, colons, dashes, ellipses, question marks, and exclamation marks, examining how their strategic deployment shapes the reader’s experience and informs performance. Ultimately, this study aims to illuminate the complex interplay between punctuation, language, and dramatic expression.